Fast link-establishment method of integrated of communication and detection based on short-wave digital channelization - Guojun LI; Cuiling XIANG; Changrong YE; Zunli WANG (Tongxin xuebao)
A link-establishment method based on short-wave digital channelized receiver was proposed for the traditional automatic link establishment technology in short-wave communications with the low accuracy of frequency selection, low efficiency of link establishment, and low utilization of resources, etc.The parallel receiving mechanism for full frequency band in short-wave communications was realized by using digital channelization.An integrated waveform of communication and detection was designed to deal with the time redundancy and equipment compatibility problems caused by waveform switching during link establishment.A fast link-establishment method was designed, to achieve a fast and robust connection in complex electromagnetic environments.The results show that the channelized structure can enhance the receiving performance of the link-establishment system, the link-establishment method has obvious advantages, channel parameter estimation method has a high estimation accuracy compared to the traditional link-establishment method and the applicability of the proposed method in practical short-wave channel environment is verified.